Pengukuran Efektivitas Mesin Produksi Besi Bondeck pada Industri Manufaktur dengan Overall Equipment Effectiveness - St Nugroho Kristono; M Hudori (JURNAL CITRA WIDYA EDUKASI, 2019)
Effectiveness is a measure of the comparison of the quantity of product produced over a period of time to a theoretical capacity, which shows the productivity of the machine. The success of the maintenance system with this TPM can be measured using Overall Equipment Effectiveness (OEE), which will show how capable a machine is to produce a quality product compared to the must. The purpose of this research was to determine the OEE value of bondeck production machine. This research was conducted in January – March 2018 in a manufacturing company located in Bekasi. The research population is the entire production on the machine, while the sample is production during January – March 2018. Data collection is done by means of observation, interview and company document tracking. Data processing is done with the Nakajima formula. The result of the research showed that the OEE value of the bondeck production machine was 53.29% in January; 48.23% in February; and 58.88% in March. This means that the company is only able to produce products from these machines, about half of the total product they are supposed to.